Aspectos toxicológicos do bissulfito e outros agentes tóxicos sobre a síntese de glicerol-3-fosfato desidrogenase citoplasmá tica de levedura de panificação - Gattas, Edwil Aparecida de Lucca [UNESP] (2006)
The synthesis of intracellular glycerol-3-phosphate dehydrogenase (EC 1.1.1.8) in baker's yeast was investigated in submerged culture supplied with glucose or glycerol as sole carbon sources. Inhibitors of the glycolytic pathway, Krebs cycle and respiratory chain did not stimulate glycerol-3-phosphate dehydrogenase synthesis when added in low concentrations in up 7.5 × 10 -5 mol/L. The repression exercised by glucose on the synthesis of glycerol-3-phosphate dehydrogenase in YP-glucose medium was reduced by the addition of fermentation products and of sodium bisulfite. Synthesis of the enzyme was raised 22-110%. However, in YP-glycerol medium, the addition of 0.06% (w/v) sodium bisulfite reduced (29%) the synthesis of the enzyme, while 0.012% (v/v) acetaldehyde stimulated the synthesis of glycerol-3-phosphate dehydrogenase by 12%.